PERANAN TINGKAT KECEMASAN TERHADAP MOTIVASI BERPRESTASI MAHASISWA - Hariyanto Hariyanto (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2019)
Fear and anxiety typically rise when a person is in a danger or feels threatened. These feelings, specifically anxiety, can direct a person’s behavior to gain his or her best performances and to solve problems creatively. It is aforementioned that anxiety facilitates a person to overcome difficulties and makes him/her success in his/her life. In education, it can be related on how anxiety motivates undergraduate students to strive for achievement in their study. The researcher attempted to discover how the role of difference levels of anxiety affects undergraduate students’ achievement motivation. Taylor Manifest Anxiety Scale (TMAS) test was employed to measure students’ trait anxiety and then the obtained scores were divided into three levels of anxiety, i.e. low, medium and high using standard deviation (SD). For students’ achievement motivation scores was gathered from questionnaires.